Antiviral activity of oleandrin and a defined extract of Nerium oleander against SARS-CoV-2 - Plante, Kenneth S. (Biomed Pharmacother, 2021)
With continued expansion of the coronavirus disease (COVID-19) pandemic, caused by severe acute respiratory syndrome 2 (SARS-CoV-2), both antiviral drugs as well as effective vaccines are desperately needed to treat patients at high risk of life-threatening disease. Here, we present in vitro evidence for significant inhibition of SARS-CoV-2 by oleandrin and a defined extract of N. oleander (designated as PBI-06150). Using Vero cells, we found that prophylactic (pre-infection) oleandrin (as either the pure compound or as the active principal ingredient in PBI-06150) administration at concentrations as low as 0.05 µg/ml exhibited potent antiviral activity against SARS-CoV-2, with an 800-fold reduction in virus production, and a 0.1 µg/ml concentration resulted in a greater than 3000-fold reduction in infectious virus production. The half maximal effective concentration (EC(50)) values were 11.98 ng/ml when virus output was measured at 24 h post-infection, and 7.07 ng/ml measured at 48 h post-infection. Therapeutic (post-infection) treatment up to 24 h after SARS-CoV-2 infection of Vero cells also reduced viral titers, with 0.1 µg/ml and 0.05 µg/ml concentrations causing greater than 100-fold reduction as measured at 48 h, and the 0.05 µg/ml concentration resulting in a 78-fold reduction. Concentrations of oleandrin up to 10 µg/ml were well tolerated in Vero cells. We also present in vivo evidence of the safety and efficacy of defined N. oleander extract (PBI-06150), which was administered to golden Syrian hamsters in a preparation containing as high as 130 µg/ml of oleandrin. In comparison to administration of control vehicle, PBI-06150 provided a statistically significant reduction of the viral titer in the nasal turbinates (nasal conchae). The potent prophylactic and therapeutic antiviral activities demonstrated here, together with initial evidence of its safety and efficacy in a relevant hamster model of COVID-19, support the further development of oleandrin and/or defined extracts containing this molecule for the treatment of SARS-CoV-2 and associated COVID-19 disease and potentially also for reduction of virus spread by persons diagnosed early after infection.